"Pseudo-suprascapular notch": is it a sonographic trap in suprascapular nerve block?. (3rd January 2019) - Podgórski, Michał; Rusinek, Marcelina; Cichosz, Maciej; Olewnik, Łukasz; Polguj, Michał; Grzelak, Piotr
Abstract : Background and objectives: The aim of the study was to describe the radiological anatomy of the pseudo-suprascapular notch —a structure localized at the floor of the supraspinatus fossa, just below the true suprascapular notch. In sonographic examination, it may imitate the suprascapular notch leading to misidentification of these structures. Methods: Ultrasound assessment of the suprascapular notch region was performed in 100 patients who underwent chest CT due to other indications. The presence of the suprascapular notch and the pseudo-suprascapular notch was evaluated together with their maximal width and depth using both techniques. The correlation between the dimensions of these two notches was assessed. Results: The pseudo-suprascapular notch was recognized in 82 patients. In four of them the suprascapular notch could not be visualized in ultrasound due to obscuring clavicle. In all cases the pseudo-suprascapular notch contained a small artery. In comparison to the suprascapular notch, the pseudo-suprascapular notch was significantly narrower and shallower, except for 10 cases with vestigial suprascapular notch where the pseudo-suprascapular notch was the only hollow in this region. The dimensions of both structures did not correlate with each other. Finally, the pseudo-suprascapular notch did not present any significant asymmetry (p=0.1185) or sexual dimorphism (43 women vs 38 men, p=0.2025). Conclusions: The pseudo-suprascapular notch is a hollow for nutrient vessels that can be mistaken for the regular suprascapular notch in cases of difficult sonographic navigation.